No effect of learning from excellence on patient safety culture in a postanaesthesia care unit: a longitudinal quasi-experimental study - Gørill Birkeli; Owen Matthew Truscott Thomas; Randi Ballangrud; Ellen Catharina Tveter Deilkås; Anne Karin Lindahl (BMC Health Services Research, 2026)
Abstract Background The prevailing strategy for combating surgically related adverse events (AEs) is to anticipate and prevent them by learning from adverse events (Safety-I). However, not all AEs can be anticipated or prevented in complex systems. This requires more focus on how daily work succeeds, that is, resilient and adaptive behaviour (Safety-II). Learning from success and promoting a positive patient safety culture (PSC) are key global strategies for eliminating preventable AEs. As a patient safety initiative, Learning from Excellence (LfE) captures episodes of successful everyday work and is thus, a system for applying a Safety-II perspective. However, its effect on PSC has not been evaluated. This study aimed to explore whether the implementation of LfE in a postanaesthesia care unit over a 16-month period changed the nurses’ perceptions of the measurable PSC dimensions ‘work engagement’, ‘teamwork climate’, ‘working conditions’ and ‘safety climate’. Methods This longitudinal two-group, controlled quasi-experimental study used an annual ‘Hospital Staff Survey’ to measure PSC factors before (2021–2022) and after (2023–2024) the implementation of LfE. The study included nurses from the surgical department of a Norwegian university hospital working in units specialised in postoperative care (intervention unit) and intensive care (comparison unit). The primary outcomes were binarised versions of individuals’ positive responses to Likert-type statements regarding ‘work engagement’, ‘teamwork climate’, ‘working conditions’ and ‘safety climate’. The data were analysed using logistic regression methods. Results Relative to the changes in the comparison unit, the results within the intervention unit indicated non-significant small positive changes in ‘work engagement’, ‘teamwork climate’ and ‘working conditions’ and a non-significant small negative change in ‘safety climate’. Conclusions LfE did not have a significant effect on PSC after 16 months implementation. Further longitudinal experimental studies are needed to measure the effect of LfE on PSC. Future research should focus on the role of psychological safety in LfE and assess whether reflexive spaces add value to LfE. Trial registration ClinicalTrials.gov NCT05794490; registered date: 4 March 2023.